SYNERGY OF DEMOCRACY, ENVIRONMENT, GENDER EQUALITY, AND INVESTMENT IN INCLUSIVE ECONOMIC DEVELOPMENT - Fadilla, Meita Indah; Kusumastuti, Sri Yani (JURNAL ECONOMICA : Research of Economic And Economic Education, 2024)
AbstractInclusive economic development is a target that Indonesia must achieve in realizing social welfare. To achieve this target, synergy must be carried out through various mutually supporting factors, namely democracy, environmental quality, gender equality, and investment. The existence of these factors has a strong influence on encouraging the realization of inclusiveness in development. This research aims to analyze the existence of democracy, environmental quality, gender inequality, and investment in inclusive economic development. The research method used was Least Squares Dummy Variable (LSDV) with a sample of 34 provinces in Indonesia in 2018-2022. The results of this study show that the presence of democracy and investment influence inclusive economic development in a significantly positive way. This means that environmental quality and gender inequality affect inclusive economic development in a significant negative way. The influence exerted by democracy, environmental quality, gender inequality, and investment of 83.54% on inclusive economic development and sustainability of 16.46% is influenced by other components not in the research model.JEL Classification: J16, P48, O11Keywords: Democracy, Environment, Gender Equality, Investment, Inclusive Economy